Hubungan Antara Kelekatan Teman Sebaya dengan Kesejahteraan Psikologi pada Siswa Kelas VII & VIII di MTS NU Candi Pasca Pandemi Covid-19 - Agustina, Miranti (ResearchJet Journal of Analysis and Inventions, 2024)
This study aims to examine the relationship between peer attachment and psychological well-being in students at MTS NU Candi after the Covid-19 pandemic. This study used class VII & VIII students as research respondents. The variables in this study are peer attachment and psychological well-being. Data analysis uses product moment correlation assisted by SPSS 26. The results of data analysis describe an R Square of 0.125, so it can be concluded that there is an influence between peer attachment to psychological well-being of 12.5%. From the results of the hypothesis testing it was found that the correlation coefficient showed the result rxy = 0.354 with peer attachment having a Sig value. 0.000, while the psychological well-being value is Sig. 0.000. This shows that there is a positive relationship between peer attachment and psychological well-being. This positive relationship can be eliminated if peer attachment is high, psychological well-being is also high, and vice versa if the lower the level of peer attachment, the lower the level of psychological well-being in students.